Integrasi Human-Tech dalam Manajemen Sumber Daya Manusia Mahasiswa untuk Meningkatkan Motivasi dan Disiplin Akademik Perguruan Tinggi - Erlin Setyaningsih (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
This research was conducted to analyse the integration of human and technological aspect in student as human resource management (HRM) to improve academic motivation and discipline in higher education. The rationale of this research is the phenomenon of increasing digitalization of education that has not been fully balanced by character development and the intrinsic motivation of students. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, participatory observation, and documentation analysis of students, lecturers, and administrative staff at universities that have implemented technology-based academic management systems. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that the implementation of technology such as Learning Management System (LMS) and academic monitoring systems has a positive impact on the efficiency and accessibility of information, but its success is greatly influenced by intrinsic motivation and discipline of students. Effective human-tech integration requires a balance between technological innovation and character development through mentoring, coaching, and interpersonal feedback. The study's conclusion confirms that the success of human-tech-based student human resource management is determined not only by technological advancements, but also by the university's ability to build a humane, communicative academic environment that is oriented toward strengthening disciplinary values ​​and fostering sustainable learning motivation.